PERBANDINGAN LATIHAN SET SHOOT PADA AREA FREE THROW DENGAN MENGGUNAKAN REPETISI BERUBAH SET TETAP DAN REPETISI TETAP SET BERUBAH TERHADAP HASIL FREE THROW PADA PESERTA EKSTRAKURIKULER BOLA BASKET PUTRA SMA NEGERI 1 KAJEN KABUPATEN PEKALONGAN TAHUN 2013/20 (Department of Physical Education, Sport, Health and Recreation, 2015)
purpose of this study are: 1 ) To determine the effect of exercise sets reps shoot using change sets and reps remain fixed set of changes to the free throw shooting results , 2 ) To determine the effect of a more effective workout between sets shoot using repeisi changing sets and reps remain fixed set of changes to the results of free throw shooting . The method used was experimental with MS pattern ( matching by subject design) . The results of the study SPSS for windows release 16.00 is a description of the data shows the average ( mean ) before exercise sets reps shoot using a fixed set of changes was 3.12 . Average ( mean ) after exercise sets reps shoot using change sets fixed at 5.13 . Based on the results of this study concluded that there was the influence of exercise on the area set shot shoot free throw by using repetition changing sets and reps remain fixed set of changes to the results of free throw shooting ( free throws ) in the men's basketball extracurricular participants SMA Negeri 1 Kajen , Pekalongan in 2013 / 2014 and the exercise sets reps shoot using a fixed set of changes which have more effective results .